Safety and immunogenicity of the Cuban heptavalent pneumococcal conjugate vaccine in healthy infants. Results from a double-blind randomized control trial Phase I. Issue 32 (6th August 2018) - ,; ,; Ruiz, Carmen R.; García, Yarmila; del Valle-Rodríguez, Rafael; Rodríguez-Concepción, Ada; Vega, Dania; Mesa, María E.; Broche, José A.; Pérez, Amarilis; Echemendía, Vladimir; Martínez, Marisel; et al.
Abstract: Background: Cuba has a new pneumococcal conjugate vaccine candidate (PCV7-TT). This study evaluates the safety and immunogenicity in healthy infants using 2p+1 vaccination schedule. Methods: A phase I, controlled, randomized and double blind clinical trial was designed. 30 unvaccinated healthy infants were included. 20 subjects were assigned to study group (PCV7-TT) and 10 to control group (Synflorix®) to receive the vaccines at 7, 8 months of age (primary series) and 11 months (booster dose). Blood samples were collected 30 days after second dose and post booster for antibodies measure analysis by ELISA and OPA. The statistics analysis included the frequency of occurrence for adverse events and the immune response. Non-parametric tests were used to compare the immune response. The clinical trial was published in the Cuban Public Register of Clinical Trials with code RPCEC00000173 available at http://registroclinico.sld.cu . Results: Overall, the safety profile of PCV7-TT was similar to Synflorix®. Local reactions were predominant and systemic events were mild in severity. Swelling and redness were frequently associated with PCV7-TT mainly after the first dose (50% and 40% respectively). 15% and 10% of subject reported severe swelling after first dose with PCV7-TT and after second dose with Synflorix®. Mild fever (≥38–≤39), vomiting and sleep disturb were the systemic events reported. 100% of infants achieved pneumococcal IgG antibody concentrations ≥0.35 µg/ml after booster dose for serotypes 1, 14, 18C and 19F in each vaccine group. For serotypes 5, 6B and 23F, more than 80% infants vaccinated with Synflorix® or PCV7-TT achieved protective IgG GMC ≥ 0.35 µg/ml after booster dose. OPA proportion's responders to the seven common serotypes were 89.5% or more after the primary dose and 100% after booster dose in vaccinated with PCV7-TT. Conclusions: The Cuban PCV7-TT is safe, well tolerated and immunogenic in healthy infants.